2009
DOI: 10.1037/a0013031
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual bounce-inducing effect: Attention alone does not explain why the discs are bouncing.

Abstract: Two discs moving from opposite points in space, overlapping and stopping at the other disc's starting point, can be seen as either bouncing or streaming through each other. With silent displays, observers report the discs as streaming, whereas if a sound is played when the discs touch each other, observers report the discs as bouncing. The origin of the switch from streaming to bouncing response is not known yet. The sound either shifts perception toward that of an impact-elastic event (i.e., a bounce) or subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 35 publications
11
63
1
Order By: Relevance
“…Because the full explanation for these findings remains undetermined, other members of our research team are currently exploring this issue to further understand the underlying differences in the perceptual processing of tones differing only in their amplitude envelopes. This work will complement and extend previous studies demonstrating the effect of amplitude envelope in a variety of auditory perception tasks (Grassi & Casco, 2009;Neuhoff, 2001;Schlauch, Ries, & DiGiovanni, 2001). …”
Section: Amplitude Envelope Affects Experimental Outcomessupporting
confidence: 68%
See 2 more Smart Citations
“…Because the full explanation for these findings remains undetermined, other members of our research team are currently exploring this issue to further understand the underlying differences in the perceptual processing of tones differing only in their amplitude envelopes. This work will complement and extend previous studies demonstrating the effect of amplitude envelope in a variety of auditory perception tasks (Grassi & Casco, 2009;Neuhoff, 2001;Schlauch, Ries, & DiGiovanni, 2001). …”
Section: Amplitude Envelope Affects Experimental Outcomessupporting
confidence: 68%
“…As sounds with different amplitude envelopes can lead to qualitatively different outcomes on a variety experiments (Grassi & Casco, 2009;Schutz & Kubovy, 2009b;Schutz & Lipscomb, 2007;Schutz & Stefanucci, 2010;Vallet et al, 2014), it is worthwhile to ponder the degree to which features of the sounds used in research should parallel features of the sounds heard in natural situations. Amplitude envelope is a parameter no less important than other stimulus characteristics more commonly defined within our survey (i.e., spectral information, duration and/or sound intensity), and likely more important than others (i.e., the specific model of tone generators and headphones/speakers used to deliver a pure tone).…”
Section: Broader Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bounce percepts increase significantly more when a decaying, impact-like sound occurs concurrent with the dots' overlap than when this sound increases in amplitude by a similar amount (Grassi & Casco, 2009). This suggests that amplitude envelope, in acting as a cue for event identification, helps facilitate integration of auditory and visual signals.…”
Section: Introductionmentioning
confidence: 99%
“…However, this tendency appears to be more readily perturbed in chimpanzees. Previous studies have identified multiple factors that can alternate stream/bounce perception (Bertenthal et al, 1993;Grassi & Casco, 2009;Kawabe & Miura, 2006;A. B. Sekuler & R. Sekuler, 1999;K.…”
Section: Discussionmentioning
confidence: 99%